2022
DOI: 10.1097/md.0000000000031320
|View full text |Cite
|
Sign up to set email alerts
|

Rate and risk factors of metabolic components and component combinations according to hypertension status in Tibetans in a cross-sectional study

Abstract: To estimate the prevalence of metabolic syndrome (MS) and metabolic components and their associated factors and component combinations according to hypertension status in Tibetans living at high altitude. Multistage sampling of 1473 participants (799 hypertensive patients and 674 normotensive subjects). MS prevalence and the number of metabolic components ≥ 3 were significantly higher in the hypertensive than normotensives. In hypertensive patients, the most common component was central obesity and it combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Hu J et al in a multistage sampling reported that the MetS prevalence and the number of metabolic components ≥ 3 were significantly higher in the hypertensive than in normotensives. 32 According to Tofano et al, when compared with patients with low CRP (< 0.1 mg/dL), those with a high CRP (≥ 0.1 mg/dL) had a significantly higher prevalence of visceral obesity, elevated triglyceride, lower HDL-C, hypertension, impaired FBG, and a higher prevalence of MetS. Moreover, most of the hypertensive patients (93.33%) presented with MetS and were related to the presence of more severe lesions in the arteries and had passed through more invasive procedures like angioplasty and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Hu J et al in a multistage sampling reported that the MetS prevalence and the number of metabolic components ≥ 3 were significantly higher in the hypertensive than in normotensives. 32 According to Tofano et al, when compared with patients with low CRP (< 0.1 mg/dL), those with a high CRP (≥ 0.1 mg/dL) had a significantly higher prevalence of visceral obesity, elevated triglyceride, lower HDL-C, hypertension, impaired FBG, and a higher prevalence of MetS. Moreover, most of the hypertensive patients (93.33%) presented with MetS and were related to the presence of more severe lesions in the arteries and had passed through more invasive procedures like angioplasty and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Further, LiFePO 4 @C NF cathodes with mesoporous structure were also successfully fabricated ( Figure a–d), which facilitated the diffusion of liquid electrolytes and maintained the structural stability of LiFePO 4 particles during lithiation/delithiation. [ 48 ] The electrode delivered a capacity of 107 mA h g −1 at 10 C and maintained 105 mA h g −1 after 200 deep charge/discharge cycles with a high capacity retention of 98% (Figure 4e). In the lattice of LiMPO 4 , Li ions have only 1D transmission paths.…”
Section: Nf Cathodes For Libsmentioning
confidence: 99%
“…e) Cycling performance at 10 C. Reproduced with permission. [ 48 ] Copyright 2017, Elsevier. f) SEM image of LiFePO 4 /CF.…”
Section: Nf Cathodes For Libsmentioning
confidence: 99%